Olopatadine Suppresses the Migration of THP-1 Monocytes Induced by S100A12 Protein - Kazuya Kishimoto; Satoshi Kaneko; Kenji Ohmori; Tadafumi Tamura; Kazuhide Hasegawa (Mediators of Inflammation)
Olopatadine hydrochloride (olopatadine) is an antiallergic drug with histamine H1 receptor antagonistic activity. Recently, olopatadine has been shown to bind to S100A12 which is a member of the S100 family of calcium-binding proteins, and exerts multiple proinflammatory activities including chemotaxis for monocytes and neutrophils. In this study, we examined the possibility that the interaction of olopatadine with S100A12 inhibits the proinflammatory effects of S100A12. Pretreatment of olopatadine with S100A12 reduced migration of THP-1, a monocyte cell line, induced by S100A12 alone, but did not affect recombinant human regulated upon activation, normal T cell expressed and secreted (RANTES)-induced migration. Amlexanox, which also binds to S100A12, inhibited the THP-1 migration induced by S100A12. However, ketotifen, another histamine H1 receptor antagonist, had little effect on the activity of S100A12. These results suggest that olopatadine has a new mechanism of action, that is, suppression of the function of S100A12, in addition to histamine H1 receptor antagonistic activity.